Synthesis and characterization of new aromatic polyesters containing biphenyl side groups - Honkhambe, Pandurang N.; Avadhani, C. V.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2007)
Aromatic polyesters containing biphenyl side groups were synthesized by phase-transfer catalyzed interfacial polycondensation of 1-(4-biphenylyl)-1,1-bis(4-hydroxyphenyl) ethane (BBHPE) with terephthaloyl chloride (TPC), isophthaloyl chloride (IPC), and a mixture of TPC/IPC (50: 50 mol ratio). Copolyesters were synthesized by utilizing different molar proportions of BBHPE and 4,4-isopropylidenediphenol (BPA) with IPC and TPC. The inherent viscosities of polyesters were in the range 0.44-1.26 dL/g. All the polyesters were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetamide, and 1-methyl-2-pyrrolidmone. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. WAXD measurements indicated that all the polyesters and copolyesters were amorphous in nature. Glass transition temperature of polyesters were in the range 198-256 degrees C, while the initial degradation temperature of polyesters were in the range 444-481 degrees C. Copolyesters derived from BBHPE exhibited improved solubility and higher glass transition temperatures compared to the corresponding polyesters based on BPA. (c) 2007 Wiley Periodicals, Inc.
Keywords: Aromatic polyesters; biphenyl side groups

Synthesis and characterization of new aromatic polyesters containing pendent naphthyl units - Honkhambe, Pandurang N.; Biyani, Mahesh V.; Bhairamadgi, Nagendra S.; Wadgaonkar, Prakash P.; Salunkhe, Manikrao M. (Journal of Applied Polymer Science, 2010)
Two bisphenols, viz., 4,4'-[1-(2-naphthaleny-1)ethylidene]bisphenol and 4,4'-[1-(2-naphthalenyl) ethylidene]bis-3-methylphenol were prepared by condensation of commercially available 2-acetonaphthanone with phenol and o-cresol, respectively. A series of new aromatic polyesters containing pendent naphthyl units was synthesized by phase-transfer-catalyzed interfacial polycondensation of these bisphenols with isophthaloyl chloride, terephthaloyl chloride, and a mixture of isophthaloyl chlorideiterephthaloyl chloride (50 : 50 mol %). Inherent viscosities of polyesters were in the range 0.83-1.76 dL g(-1), while number average molecular weights (M(n)) were in the range 61,000-235,000 g mol(-1). Polyesters were readily soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, m-cresol, pyridine, N,N-dimethylformamide, N,N-dimethylacetarnide, and 1-methyl-2-pyrrolidinone at room temperature. Tough, transparent, and flexible films were cast from a solution of polyesters in chloroform. X-Ray diffraction measurements displayed a broad halo at 20 congruent to 19 degrees indicating the amorphous nature of polyesters. Glass transition temperatures of polyesters were in the range 209-259 degrees C. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of polyesters was in the range 435-500 degrees C indicating their good thermal stability. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 117: 2545-2552, 2010
Keywords: Aromatic polyesters; bisphenol; interfacial polycondensation; pendent naphthyl units

Synthesis and characterization of polyesters from 2,3-bis (4 `-hydroxy phenyl) quinoxaline and 2,3-bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline - Patil, V. B.; Medhi, M.; Bhairamadgi, Nagendra S.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
Two bisphenols containing pendant, quinoxaline moiety; 2,3-bis (4'-hydroxy phenyl) quinoxaline (BHPQ) and 2,3-bis (2'-hydroxynaphthalene-6-yl) quinoxaline (BHNQ) were synthesized and characterized by FT-IR, (1)H, (13)C NMR and mass spectrometry. Aromatic polyesters and copolyesters were prepared by interfacial polymerization from BHPQ or BHNQ and isophthaloyl chloride or terephthaloyl chloride or a mixture of different mole proportions of (IPC + TPC). These polyesters and copolyesters were characterized by spectroscopic technique, viscosity measurement, solubility, thermal stability. DSC and XRD. Polymers had moderate to high molecular weights as evidenced by the inherent viscosities in the range 0.35-0.78 dL/g for BHPQ series and 0.27-0.52 dL/g for BHNQ series. BHPQ polyesters and copolyesters dissolved in m-cresol, NMP and conc. H(2)SO(4) whereas, BHNQ polyesters and copolyesters were readily soluble in NMP, DMAc, (TCE + phenol) and partly soluble in solvent like CHCl(3), pyridine, etc. Wide angle X-ray diffraction (WAXD) results showed that introduction of quinoxaline moiety into polymer chain and aromatic phenyl/rigid naphthyl structures lead to crystalinity. Differentional scanning calorimetry of BHNQ polyesters showed the glass transition temperatures in the range of 131-151 degrees C. BHPQ polyesters did not show any weight loss below 330 degrees C and retained 27-55% weight at 900 degrees C when investigated by TGA under nitrogen atmosphere demonstrating good thermal stability BHNQderived polyesters showed initial decomposition temperatures in range 211-234 degrees C. The structure-property relationships for the mentioned polyesters are analyzed, as these polyesters are of interest as materials for electronics, microelectronics and membrane separation. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: 2; 3-Bis (2 `-hydroxynaphthalene-6 `-yl) quinoxaline; 3-Bis (4 `-hydroxy phenyl) quinoxaline; Aromatic polyesters; Glass transition temperature; solubility; Thermal properties

Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization - Tawade, Bhausaheb V.; Salunke, Jagadish K.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2014)
A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50: 50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co) polyesters exhibited inherent viscosities in the range 0.70-1.21 dL g(-1) and number-average molecular weights in the range 16,000-48,200 (GPC, polystyrene standard). Polyesters were soluble in common organic solvents such as chloroform and dichloromethane and could be cast into films from chloroform solution. Polyesters exhibited T-10 values in the range 430-455 degrees C and Tg values were in the range 29-202 degrees C. Dynamic mechanical storage modulus and maximum on transition of tan delta curve decreased with increased content of HPPDP in copolyesters. Importantly, the large difference between Tg and T-10 values offers the possibility to process these polyesters in the melt.
Keywords: Aromatic polyesters; Cashew nut shell liquid; pentadecyl; Polycondensation; processability; Thermal properties

Aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups: synthesis and characterization - Bapat, Snehalata P.; Jadhav, Sushilkumar A.; Valsange, Nitin G.; Tawade, Bhausaheb V.; Honkhambe, Pandurang N.; Chavan, Nayaku N.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2017)
A new bisphenol, 1,1-bis-[(4-hydroxyphenyl)-1-(4-phenylsulfonyl) phenyl)] ethane (DPSBP) was synthesized starting from diphenylsulfide and was characterized by spectroscopic methods. DPSBP was polycondensed with isophthalic acid chloride (IPC), terephthalic acid chloride (TPC) and a mixture of IPC and TPC (50: 50 mol%) by phase-transfer catalysed interfacial polymerization method to obtain aromatic polyesters containing pendent 4-(phenylsulfonyl)phenyl groups. A series of copolyesters was also obtained by polycondensation of varying molar proportions of DPSBP and bisphenol-A (BPA) with TPC. (Co) polyesters exhibited inherent viscosities in the range 0.56-1.57 dLg(-1) and number average molecular weights (Mn) were in the range 28,650-80,230 g/mol. Polyesters dissolved readily in common organic solvents such as dichloromethane, chloroform, tetrahydrofuran and aprotic polar solvents such as N-methylpyrrolidone, and N, N-dimethylacetamide. Tough, transparent and flexible films of polyesters could be cast from their chloroform solutions. X-Ray diffraction studies indicated amorphous nature of aromatic polyesters. Polyesters showed T-g values in the range 223-257 degrees C while T-10 values were in the range of 469-484 degrees C indicating their excellent thermal stability.
Keywords: Aromatic polyesters; Bulky pendent group; solubility; thermal stability

Utilization of bisphenol based on lignin-derived chemicals for the synthesis of partially bio-based aromatic copolyesters - Wale, Apparav K.; Ambade, Ashootosh V.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
New aromatic copolyesters were synthesized by phase-transfer catalyzed interfacial polycondensation of 4,4 `-((3,4-dimethoxyphenyl)methylene)bis(2-methoxyphenol) (DMBM) with isophthaloyl chloride (IPC) and a mixture of (50:50 mol %) IPC and terephthaloyl chloride (TPC). Additionally, a series of copolyesters was synthesized by polycondensation of varying compositions of DMBM and bisphenol A with IPC. Copolyesters exhibited inherent viscosity and Mn values in the range 0.59-0.98 dL/g and 15,840-49,460 g/mol, respectively, indicating formation of reasonably high molecular weight polymers. Copolyesters could be cast into tough, transparent and flexible films from chloroform solution. UV-vis measurements on films gave values of T400, T450 and cut-off wavelength in the range 80-84 %, 83-89 % and 324-334 nm, respectively. The formation of random copolyesters was evidenced by 13C NMR spectroscopic studies. Copolyesters exhibited good thermal stability with 10% weight loss temperature in the range 391-438 degrees C. The Tg values of copolyesters were in the range 162-180 degrees C and Tg values decreased with an increase in mol% content of DMBM. Copolyesters exhibited tensile strength, Young's modulus and elongation at break values in the range 83.55-70.68 MPa, 2.11-1.31 GPa and 10.52-5.45 %, respectively.
Keywords: Aromatic polyesters; bio-based; bisphenol; methoxyl; Thermal properties